Training on Making Organic Compost Using the Takakura Method and Its Application to Vegetable Crops in Punggur Kecil Village, Kubu Raya Regency - Dwi Zulfita; Setia Budi; Surachman Surachman; Agus Hariyanti (STKIP Singkawang, 2022)
The data and results of field observations show that Punggur Kecil Village is identical to the economically weak community and depends on agriculture for its livelihood, which in cultivating plants using inorganic fertilizers. Inorganic fertilizers are widely used by farmers, this is because they are more efficient and effective than organic fertilizers. Whereas the continuous use of chemical fertilizers causes the land to be damaged and cannot provide carrying capacity for human life. This happens because the community does not have the knowledge and skills in processing household waste into organic fertilizer that is more environmentally friendly. Therefore, the abundance of natural resources in Bilayuk Village from the agricultural aspect cannot be utilized optimally due to limited human resources. The results showed that the material for processing household waste into organic compost using the Takakura method could be understood by 68% of the target audience, overall participants liked the use of Takakura compost in vegetable crop cultivation, with 14% of participants who preferred inorganic fertilizers, 27 % prefer Takakura's organic compost, and 59% like both